CPF Induces GC2spd Cell Injury via ROS/AKT/Efcab6 Pathway - Xuelian Zhang; Mengyang Zhang; Chunzhi Wang; Qingchuan Song; Haiyan Yang; Qi Tang; Qiaoling Zhao; Jing Wang; Chuanying Pan (Cells, 2025)
Chlorpyrifos (CPF) has been extensively utilized in recent decades due to its highly efficient insecticidal properties. However, the widespread use of pesticides has posed new challenges to male reproduction. This study aims to explore the potential molecular mechanisms of male reproductive decline induced by CPF. We employ flow cytometry, qRT-PCR, Western blot, RNA sequencing, and bioinformatics analysis to investigate the potential molecular mechanisms involved in CPF-induced male reproductive damage in GC2spd cells. Our results revealed that after 24 h of CPF treatment, the cell viability, cell cycle, apoptosis, and reactive oxygen species (ROS) accumulation of GC2spd cells were significantly affected in vitro. RNA sequencing analysis data indicated that a total of 626 genes were differentially expressed compared to the DMSO group, especially for Efcab6, Nox3, and Cmpk2. These differential genes were mainly enriched in signaling pathways such as PI3K-AKT and glutamine metabolism. In addition, further validation through qRT-PCR, Western blot, and experiments involving the inhibition of intracellular ROS generation with N-acetylcysteine collectively confirmed that CPF induces male reproductive damage through the ROS/AKT/Efcab6 pathway. These studies elucidate potential targets and molecular mechanisms underlying CPF-induced male infertility, providing a theoretical basis for the prevention of male reproductive damage caused by pesticide residues.